149k views
0 votes
Solve for x.

3x^2-4x-2=0

Enter your simplified answers, as exact values, in the boxes

User Padfoot
by
6.2k points

2 Answers

3 votes

Answer:


x = (2)/(3) + (√(10) )/(3) , x = (2)/(3) - (√(10) )/(3)

Explanation:

Multiplying the coefficient of x by the constant to get:

3 x (-2) = -6

Find factors of -6 that equal the middle term -4.

Since, no such factors can be found so we can solve the equation by completing the square.

To complete the square, divide the equation by the coefficient of x^2 which is 3 to get:


x^(2) - (4)/(3) x - (2)/(3) = 0


x^(2) - (4)/(3) x = (2)/(3)

Now divide the coefficient of x by 2 and add the square of the result to both sides of the equation:


x^(2) - (4)/(3) x + (-(2)/(3) )^(2) = (2)/(3) +  (-(2)/(3) )^(2)


(x - (2)/(3) )^2 = (2)/(3) + (4)/(9)


(x - (2)/(3) )^2 = (4)/(9)


\sqrt{(x - (2)/(3) )^2} = \sqrt{(4)/(9) }


x - (2)/(3) = \sqrt{(10)/(9) } ,
x - (2)/(3) = -\sqrt{(10)/(9) }


x = (2)/(3) + (√(10) )/(3) , x = (2)/(3) - (√(10) )/(3)



User Suugaku
by
5.8k points
6 votes
ANSWER


x=\frac{2-√(10)} {3}

or


x=\frac{√(10)+2} {3}

We have


3x^2-4x-2=0

Since we cannot factor easily, we complete the square.

Adding 2 to both sides give,


3x^2-4x=2

Dividing through by 3 gives


x^2-(4)/(3)x= (2)/(3)

Adding
(-(2)/(3))^2 to both sides gives


x^2-(4)/(3)x+(-(2)/(3))^2= (2)/(3)+(-(2)/(3))^2

The expression on the Left Hand side is a perfect square.


(x-(2)/(3))^2= (2)/(3)+(4)/(9)


\Rightarrow (x-(2)/(3))^2= (10)/(9)


\Rightarrow (x-(2)/(3))=\pm \sqrt{(10)/(9)}


\Rightarrow (x)=(2)/(3) \pm {(√(10))/(3)

Splitting the plus or minus sign gives


x=\frac{2- √(10)} {3}

or


x=\frac{√(10)+2} {3}
User Carnieri
by
5.5k points